Physical activity and normal body mass of women aged 45-55 - Nowak, Maria; Szczepanowska, Ewa (Anthropological Review, 2003)
The aim of this paper was to determine the degree to which physical activity in women aged 45-55 was an independent influence on body mass, as expressed by BMI, and to what degree it occurred in interaction with their level of education, financial status, and self-evaluated physical efficiency and health status. The material consisted of 212 female inhabitants of three cities in Poland, participating in physical exercises for at least one year. Statistical analysis of the collected data was carried out by the χ2 test, the H test, the Mann-Whitney U test, and analysis of variance (ANOVA). A statistically significant relation between the level of physical activity and BMI values was observed. Women with a medium and high level of physical activity were most often of normal body mass, whereas women with low activity were characteristically overweight. Analysis of the data revealed that the normal body mass of women aged 45-55 was influenced by: the level of physical activity, level of education, and financial status of respondents. Physical activity was an independent factor influencing normal body mass of women, irrespective of social features (i.e., education and financial status).